2019
DOI: 10.1093/cid/ciz107
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Mycobacterium canettii Infection: A Retrospective Study of 20 Cases Among French Soldiers and Relatives

Abstract: Background Mycobacterium canettii forms part of the Mycobacterium tuberculosis complex. Mycobacterium canettii infections are mainly described in the Horn of Africa. The permanent presence of French soldiers in Djibouti raises the question of the risk of being infected with M. canettii. Here, we describe M. canettii infections among French military and their families between 1998 and 2015. Methods This retrospective study rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…However, given that Group A appeared to be most susceptible and Group D (M. canettii) is exceptionally rare globally, neither group were our focus. 36 Feuerriegel et al 16 had previously reported that M. canettii is less susceptible to pretomanid. Here, we tested a total of 21 M. canettii strains across two laboratories and consistently obtained MICs of 2-4 mg/L.…”
Section: Clinical Strainsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, given that Group A appeared to be most susceptible and Group D (M. canettii) is exceptionally rare globally, neither group were our focus. 36 Feuerriegel et al 16 had previously reported that M. canettii is less susceptible to pretomanid. Here, we tested a total of 21 M. canettii strains across two laboratories and consistently obtained MICs of 2-4 mg/L.…”
Section: Clinical Strainsmentioning
confidence: 97%
“…The provisional CC of 1 mg/L set by EMA is too high for Groups A and B and too low for Groups C and D. 2 Fewer than 200 cases of M. canettii infection (Group D) have been described to date, mostly from patients with links to the Horn of Africa. 36 Consequently, it is unlikely that robust clinical evidence for pretomanid treatment in this group will ever become available. In contrast, L1 strains (Group C) are estimated to account for 28% of the global TB burden.…”
Section: Intrinsic Mtbc Susceptibility To Pretomanidmentioning
confidence: 99%
“…In this regard, the role of the cell envelope lipids in the transition of environmental mycobacteria becoming highly transmissible, pathogenic and host-dependent is pointed out (102). The possibility that ancient M. tuberculosis complex strains such as M. canettii, mainly isolated in the horn of Africa (172,173), have evolved has been explored, that is, changing their metabolism and increasing their cell envelope hydrophobicity as they evolved to the modern M. tuberculosis complex strains, e.g., changing their cell envelope's outmost exposed lipid polarity and thus evolving into a more hydrophobic organism. This was achieved by stopping the production of polar lipids such as LOSs or PGLs (which currently are just described in a subset of M. tuberculosis complex modern strains, Beijing clinical isolates), reducing their polarity (e.g., by losing sugars or adding acyl chains in their cell envelope glycolipids, e.g., DAT, TAT, PAT, SLs, TDM, TMM), and increasing the presence of apolar lipids in their cell envelopes [e.g., dimycocerosates of the phthiocerol family (PDIMs)] (102).…”
Section: The Role Of Cell Envelope Glycolipids In M Tuberculosis Evomentioning
confidence: 99%
“…Given the highly recombinogenic nature of M. canettii, it is not surprising that this species yields two different patterns (10,11). All representatives of this species, including the two strains that gave the new binding pattern experimentally and in silico, have been found to be resistant to pyrazinamide when tested with the Bactec MGIT 960 at 100 g/ml, the only critical concentration recognized by the Clinical and Laboratory Standards Institute and the World Health Organization (WHO) (9,(12)(13)(14)(15)(16)(17). Although it is unclear whether this phenotype is due to a single mechanism shared by all strains (e.g., rpsA T5A) or whether different mutations are responsible in different strains (e.g., panD M117T or a series of pncA mutations [Table S3]), we recommend that the package insert is updated to include this novel pattern as "M. canettii (intrinsically resistant to pyrazinamide)" (14, 18-20).…”
mentioning
confidence: 99%